Perspektif Kitab Pengkhotbah terhadap Etos Kerja dan Implikasinya pada Mahasiswa Sekolah Teologi - Cristine Natalia; Gandi Wibowo (LPPM STT Baptis Kalvari, 2024)
This article explores theological school students’ perspectives on the Book of Ecclesiastes (Qoheleth) which influences the formation of their work ethic. Research reveals how understanding the Book of Ecclesiastes influences their attitudes and views toward work, calling, and spiritual ministry. The Book of Ecclesiastes is sometimes misunderstood as a book that emphasizes pessimism, but analysis shows that the message conveyed is actually realistic. The Book of Ecclesiastes actually teaches the importance of responsibility, discipline and integrity at work. This research uses a qualitative method with a literature study approach but is accompanied by interviews with 30 seminary students to provide a rich diversity of student perspectives on the Book of Ecclesiastes in the context of student work ethic. The results show that many students face challenges in developing a good work ethic due to laziness, procrastinating, and other unethical actions. The discussion in this article illustrates how a correct understanding of this book can form a strong and responsible work ethic for theology students. Concrete steps such as coaching, establishing a conducive learning culture, curriculum review, and education about the importance of theological education are proposed to improve student work ethic. It is hoped that a correct understanding of the message of the Book of Ecclesiastes will help theological school students to develop a strong work ethic, integrity, and responsibility in carrying out their duties.